2010
DOI: 10.1590/s0004-282x2010000300002
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive craniectomy in massive cerebral infarction

Abstract: Twenty one patients were submitted to decompressive craniectomy for massive cerebral infarct. Ten patients (47.6%) presented a good outcome at the 6 months evaluation, eight had a poor outcome (38%) and three died (14.2%). There was no outcome statistical difference between surgery before and after 24 hours of ictus, dominant and non-dominant stroke groups. Patients older than 60 years and those who had a Glasgow Coma Scale (GCS)<8 in the pre-surgical exam presented worst outcome at six months (p<0.05). Decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 29 publications
0
12
0
3
Order By: Relevance
“…If a patient scores more than 20, it usually indicates a dense paralysis with impaired consciousness 2). NIHSS score ≥20 for left-sided infarctions, or ≥18 for right-sided infarctions may predict which patients will develop malignant edema and/or have a poor outcome 18). Lam et al16) concluded that a NIHSS score of > 22 is predictive of high mortality.…”
Section: Discussionmentioning
confidence: 99%
“…If a patient scores more than 20, it usually indicates a dense paralysis with impaired consciousness 2). NIHSS score ≥20 for left-sided infarctions, or ≥18 for right-sided infarctions may predict which patients will develop malignant edema and/or have a poor outcome 18). Lam et al16) concluded that a NIHSS score of > 22 is predictive of high mortality.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lot of controversy in this issue. While some studies have shown that nearly half of patients had good outcome after surgery with GOS scores of 4 and 5 (Mattos et al 2010; Mori et al 2004), some others have reported that surgery could not achieve significant good results (Staykov & Gupta 2011; van der Worp & Kappelle 2011). This will increase the number of severely disabled patients, imposing significant pressure over the family and the whole society (Hofmeijer et al 2009; Schneck & Origitano 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Steiger33) reported that of early neurologic findings, degree of motor paralysis and decreased mentality most importantly determine prognosis. Mattos et al22) found that a GCS score of ≤8 before surgery was associated with poorer prognosis, but Walz et al38) found that the surgical outcome of malignant MCA infarction was not related to initial NIHSS. In the present study, average preoperative NIHSS in group B was significantly lower than in group A ( p =0.019).…”
Section: Discussionmentioning
confidence: 99%